2014
DOI: 10.1167/iovs.13-13279
|View full text |Cite
|
Sign up to set email alerts
|

Development of Allele-Specific Gene-Silencing siRNAs for TGFBI Arg124Cys in Lattice Corneal Dystrophy Type I

Abstract: We have identified a lead siRNA specific to the TGFBI-Arg124Cys mutant allele associated with LCDI. Silencing of exogenous TGFBI was observed at mRNA and protein levels, and in an ex vivo model of LCDI with an efficient suppression of the endogenous mutant allele. This result indicates the potential of siRNA treatment as a personalized medicine approach for the management of heritable TGFBI-associated corneal dystrophies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…In this study the protein profile and TGFBIp processing within the stromal aggregates of patients with LCD1 and GCD1 was investigated. By further elucidating the proteins and molecular processes involved in these disease states it is hoped that current therapies under development for such conditions could take another step toward the clinic, [13][14][15][16] or novel therapies developed based on these latest findings.…”
Section: Discussionmentioning
confidence: 99%
“…In this study the protein profile and TGFBIp processing within the stromal aggregates of patients with LCD1 and GCD1 was investigated. By further elucidating the proteins and molecular processes involved in these disease states it is hoped that current therapies under development for such conditions could take another step toward the clinic, [13][14][15][16] or novel therapies developed based on these latest findings.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,16,17,36 We have also developed a potent siRNA for one of the TGFBI related corneal dystrophies. 37 Within this study, we further demonstrate the potency and specificity of the previously identified K12-Leu132Pro-9 siRNA 7 using exogenous constructs before we assess knockdown of the endogenous mutant K12 allele in our MECD corneal limbal epithelial cells.…”
Section: Discussionmentioning
confidence: 69%
“…A dual-luciferase assay was used to quantify potency and allele-specificity of the three test sgRNAs in exogenous constructs, using methods adapted as previously described. 9 , 11 , 18 In short, HEK AD293 cells (Life Technologies) were transfected using Lipofectamine 2000 (Life Technologies) with both K12WT-Luc or K12LP-Luc expression constructs and sgNSC, sgK12 or sgK12LP constructs at a ratio of 1:4. Cells were incubated for 72 h before being lysed and the activities of both Firefly and Renilla luciferase quantified.…”
Section: Methodsmentioning
confidence: 99%
“…Through use of techniques adapted from our previous research identifying therapeutic allele-specific short interfering RNAs, 7 , 9 , 10 , 11 this Cas9-based gene-editing system was found to be potent and allele specific. This study constitutes the first description of allele-specific CRISPR/Cas9 gene editing at a novel PAM created by a disease-causing heterozygous SNP.…”
Section: Introductionmentioning
confidence: 99%